When the Bough Breaks: A Father's Story - Naseef, Robert (Journal of religion, disability & health, 2002)
The diagnosis of a child with a disability is often the harbinger of psychological and spiritual crisis for parents as well as an opportunity for growth. This essay looks at the grief and the transformation from the viewpoint of a father of a child with autism and mental retardation. The writer, who is also a psychologist, explores the agonizing decision to seek a residential placement which is currently unpopular but sometimes necessary.